2014
DOI: 10.1093/ejcts/ezu078
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to long-term aortic valve-related outcomes after conventional repair for patients with interrupted aortic arch or coarctation of the aorta, combined with ventricular septal defect: the impact of bicuspid aortic valve

Abstract: The long-term outcomes after conventional repair under our criteria were acceptable. BAV was a significant risk factor for valve-related reinterventions after conventional repair for IAA/CoA with VSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
2
26
3
Order By: Relevance
“…In particular, in neonates with an aortic root z-score less than 22.5 the probability of score is 25 to 26. 11,19,20 Contrary to these studies, our study found that the aortic root size not the aortic valve annulus size increased the odds of reoperation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, in neonates with an aortic root z-score less than 22.5 the probability of score is 25 to 26. 11,19,20 Contrary to these studies, our study found that the aortic root size not the aortic valve annulus size increased the odds of reoperation.…”
Section: Discussioncontrasting
confidence: 99%
“…From this small study, it was recommended, that a LVOT bypass procedure should be considered if the aortic annulus is less than the patient's weight + 1.0 mm. Other studies based on surgeon and/or institutional preference have published that a LVOT bypass procedure such as Yasui should be considered if the absolute aortic valve annulus is 3–4 mm or less or the aortic valve annulus z ‐score is −5 to −6 . Contrary to these studies, our study found that the aortic root size not the aortic valve annulus size increased the odds of reoperation.…”
Section: Discussioncontrasting
confidence: 95%
“…The impact of bicuspid aortic valve and severe aortic valve stenosis in patients with obstructive lesions of the aortic arch on medium and long-term outcome was recently described by Sugimoto et al ( 15 ), with bicuspid aortic valve representing a risk factor for later regurgitation or stenosis.…”
Section: Discussionmentioning
confidence: 91%
“…[ 11 ] However, patients with bicuspid aortic valve and coexisting congenital heart diseases, such as an interrupted aortic arch, coarctation of the aorta, or ventricular septal defect may be more susceptible to complications than in the general population. [ 12 13 14 ] Bicuspid aortic valve morphology is a common risk factor for valve-related complications, for example, dilation of the aorta, which may be present at birth and could progress over time irrespective of the functional state of the valve. [ 5 15 16 17 18 19 ] Furthermore, bicuspid aortic valve has been identified as the root cause of aortic stenosis in 70%–85% of pediatric cases and is associated with a higher risk of infective endocarditis and acute thoracic aortic emergencies, such as aneurysm and dissection and valve-related re-intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 15 16 17 18 19 ] Furthermore, bicuspid aortic valve has been identified as the root cause of aortic stenosis in 70%–85% of pediatric cases and is associated with a higher risk of infective endocarditis and acute thoracic aortic emergencies, such as aneurysm and dissection and valve-related re-intervention. [ 2 14 20 ] Despite advances in disease management, children with congenital heart disease who survive into adulthood are at increased risk of sudden death, with a relatively high percentage of these patients having bicuspid aortic valve. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%